Moving Stimuli Facilitate Synchronization But Not Temporal Perception - Silva, Susana; Castro, São Luís (Frontiers in Psychology, 2016)
Recent studies have shown that a moving visual stimulus (e.g., a bouncing ball) facilitates synchronization compared to a static stimulus (e.g., a flashing light), and that it can even be as effective as an auditory beep. We asked a group of participants to perform different tasks with four stimulus types: beeps, siren-like sounds, visual flashes (static) and bouncing balls. First, participants performed synchronization with isochronous sequences (stimulus-guided synchronization), followed by a continuation phase in which the stimulus was internally generated (imagery-guided synchronization). Then they performed a perception task, in which they judged whether the final part of a temporal sequence was compatible with the previous beat structure (stimulus-guided perception). Similar to synchronization, an imagery-guided variant was added, in which sequences contained a gap in between (imagery-guided perception). Balls outperformed flashes and matched beeps (powerful ball effect) in stimulus-guided synchronization but not in perception (stimulus- or imagery-guided). In imagery-guided synchronization, performance accuracy decreased for beeps and balls, but not for flashes and sirens. Our findings suggest that the advantages of moving visual stimuli over static ones are grounded in action rather than perception, and they support the hypothesis that the sensorimotor coupling mechanisms for auditory (beeps) and moving visual stimuli (bouncing balls) overlap.